Technology-Integrated Collaborative Learning: Convenient Alternative in Developing the Problem Solving Capability and Positive Attitude towards Mathematics - Wawan, W; Marsigit, M; Fitria Ningsih, Eka; Widyawati, Santi; Kusumaningtyas, Wahyu; Mahmudi, M; Suhono, S; Mukhlishin, Ahmad; Ganda Putra, Fredi; Setiawan, Agus (International Journal of Engineering and Technology, 2018)
This research is aimed to describe a technology-integrated collaborative learning, exploring the student perception associated with the implemented learning method as well as observing the effectiveness of this method compared to the individual method. This research was conducted in Islamic Institute of Maâ€™arif NU Metro â€“ Indonesia in 2017/2018 academic year. Through the application of cluster random sampling technique, about 28 students were determined as the research sample. The research sample was the fifth semester students of mathematics education who are currently learning the geometric transformation subject. The experimental class which becomes the focus of researcher is consist of 28 students who were derived from the cluster random sampling technique. This research design is a mixed research. Observation sheet, interview, and test of problem solving capability were used as the data collecting instrument. The results of this research indicates that the collaborative process is performing well. The learning process was conducted in the class, not in the computer laboratory. The limited number of laptop did not impact the learning process. The observation results indicate that the level of student enthusiasm in following the learning process is adequately high. The positive comments from students show that the technology-integrated collaborative method has supported them to comprehend the mathematics concepts as well as growing the high intention of learning. Negative comments that occur are associated with the complexity of studied material and the difficulty in using the application for a small number of students. The test results of problem solving capability has shown that the method of technology-integrated collaborative learning provides better results compared to the individual learning.. Â Â